2012
DOI: 10.1007/s11142-012-9182-y
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance, compensation consultants, and CEO pay levels

Abstract: This study investigates the relation between corporate governance and CEO pay levels and the extent to which the higher pay found in firms using compensation consultants is related to governance differences. Using proxy statement disclosures from 2,110 companies, we find that CEO pay is higher in firms with weaker governance and that firms with weaker governance are more likely to use compensation consultants. CEO pay remains higher in clients of consulting firms even after controlling for economic determinant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
72
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(80 citation statements)
references
References 40 publications
8
72
0
Order By: Relevance
“…A number of studies …nd that various measures of board ine¤ectiveness are associated with pay practices that favor the CEO (Hallock, 1997;Core, Holthausen, and Larcker, 1999;Fahlenbrach, 2009;Armstrong, Ittner, and Larcker, 2012). The level of CEO pay tends to increase in board size (negatively related to the pressure an individual director faces to monitor), the number of outside directors serving on more than three boards (negatively related to their capacity to monitor), and the number of outsiders appointed by the CEO (negatively related to their independence).…”
Section: Boardsmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies …nd that various measures of board ine¤ectiveness are associated with pay practices that favor the CEO (Hallock, 1997;Core, Holthausen, and Larcker, 1999;Fahlenbrach, 2009;Armstrong, Ittner, and Larcker, 2012). The level of CEO pay tends to increase in board size (negatively related to the pressure an individual director faces to monitor), the number of outside directors serving on more than three boards (negatively related to their capacity to monitor), and the number of outsiders appointed by the CEO (negatively related to their independence).…”
Section: Boardsmentioning
confidence: 99%
“…In the …rst year after the 2006 disclosure rules required U.S. …rms to reveal the use of compensation consultants, 78% of S&P 1,500 …rms used at least one consultant (of which 17% use two or more), and another 9% purchased compensation surveys prepared by consultants (Murphy and Sandino, 2010). While using consultants is associated with higher executive pay, this di¤erence becomes insigni…cant when controlling for corporate governance (Armstrong, Ittner, and Larcker, 2012). Hence, higher pay might be caused by di¤erences in …rm characteristics, not by using consultants.…”
Section: Compensation Consultantsmentioning
confidence: 99%
See 1 more Smart Citation
“…This explains the existence of board systems (Kostyuk, 2006) and other external monitoring such as rating agencies and institutional investors. On the other hand highpowered incentive contracts such as shares and stock-options to remunerate directors were implemented in most companies over the last years (Armstrong et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Armstrong, Ittner and Larcker (2012) found that firms with weaker governance that used a remuneration consultant are more likely to pay higher than expected remuneration to the CEO. In contrast, Murphy and Sandino (2017) find that the use of a consultant is associated with more complex incentive plans, which in turn result in higher levels of pay.…”
Section: Remuneration Consultantmentioning
confidence: 95%